2018
DOI: 10.1111/chd.12721
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Noonan spectrum disorders in a pediatric population with valvar pulmonary stenosis

Abstract: Objective:To evaluate the prevalence of Noonan spectrum disorders (NSD) in a pediatric population with valvar pulmonary stenosis (vPS) and identify the clinical characteristics that differentiate those with NSD from those without NSD.Design: A retrospective chart review of 204 patients diagnosed with vPS between 9/1/2012 and 12/1/2016 at a pediatric medical center was performed. The quantitative features of vPS, genetic diagnosis information, and phenotypic characteristics of Noonan syndrome were collected. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(149 reference statements)
4
9
1
Order By: Relevance
“…NS has a high phenotypic variability (Tartaglia et al, 2002) and can present with either isolated anomalies (pulmonary stenosis), minor facial features, short stature, or multiple congenital anomalies. The incidence of NS in individuals with pulmonary stenosis appears to be higher in the Colombian population when compared to other reports (Anderson et al, 2019).…”
Section: Discussioncontrasting
confidence: 53%
“…NS has a high phenotypic variability (Tartaglia et al, 2002) and can present with either isolated anomalies (pulmonary stenosis), minor facial features, short stature, or multiple congenital anomalies. The incidence of NS in individuals with pulmonary stenosis appears to be higher in the Colombian population when compared to other reports (Anderson et al, 2019).…”
Section: Discussioncontrasting
confidence: 53%
“…In the context of CHD, the focus has been on patients with PVS as that is the commonest lesion. A study of a cohort of 204 patients with PVS found that 6% had NS (Anderson et al, ); of note, the cases with non‐syndromic PVS were not routinely tested for NS. Compared to non‐syndromic cases of PVS, those with PVS due to NS were more likely to have features associated with NS: short stature, pectus deformity, neurodevelopmental delays or other, unexpected cardiac issues such as HCM or AS.…”
Section: Diagnosing Ns In Patients With Chdmentioning
confidence: 99%
“…In the context of CHD, the focus has been on patients with PVS as that is the commonest lesion. A study of a cohort of 204 patients with PVS found that 6% had NS (Anderson et al, 2019); of note, the cases with non-syndromic PVS were not routinely tested for Gene resequencing panels will become obsolete at some point. The cost of sequencing human exomes or genomes has declined spectacularly over the past several years (Sboner, Mu, Greenbaum, Auerbach, & Gerstein, 2011).…”
Section: Relevant Comorbiditiesmentioning
confidence: 99%
“…However, institutions may perform, or at least offer, a CMA to all individuals with complex/critical CHD regardless of the presence or absence of recognized syndromic features. (Anderson et al, 2019). Heterotaxy panels with the inclusion of primary ciliary dyskinesia genes should be considered in patients with complex cardiac defects such as unbalanced atrioventricular canal defects or malposed great vessels with or without additional left-right patterning abnormalities (Geddes et al, 2020;Pierpont et al, 2018).…”
Section: Cytogenetic Testing Strategiesmentioning
confidence: 99%
“…Targeted multi‐gene panels commonly used for CHDs include RASopathy gene panels and heterotaxy gene panels. RASopathy gene panels should be considered in patients with features of Noonan‐spectrum disorders, valvar pulmonic stenosis with another cardiovascular malformation, or valvar pulmonic stenosis with specific extracardiac features (Anderson et al., 2019). Heterotaxy panels with the inclusion of primary ciliary dyskinesia genes should be considered in patients with complex cardiac defects such as unbalanced atrioventricular canal defects or malposed great vessels with or without additional left‐right patterning abnormalities (Geddes et al., 2020; Pierpont et al., 2018).…”
Section: Genetic Testing For Congenital Heart Defectsmentioning
confidence: 99%